The Use of Wavelet, DCT & Quadtree for Images Color Compression - Ahmed , Ali H.; George , Loay E. (Iraqi Journal of Science, 2022)
The need for image compression is always renewed because of its importance in reducing the volume of data; which in turn will be stored in less space and transferred more quickly though the communication channels.In this paper a low cost color image lossy color image compression is introduced. The RGB image data is transformed to YUV color space, then the chromatic bands U & V are down-sampled using dissemination step. The bi-orthogonal wavelet transform is used to decompose each color sub band, separately. Then, the Discrete Cosine Transform (DCT) is used to encode the Low-Low (LL) sub band. The other wavelet sub bands are coded using scalar Quantization. Also, the quad tree coding process was applied on the outcomes of DCT and quantization processes. Finally, the adaptive shift coding is applied as high order entropy encoder to remove the remaining statistical redundancy to achieve efficiency in the performance of the compression process.The introduced system was applied on a set of standard color image; the attained compression results indicated good efficiency in reducing the size while keeping the fidelity level above the acceptable level, where it was obtained compression ratio which is around 1:40 for Color Lena, 1:30 for color Barbara.